Laboratory Studies on Absolute n-resolved Charge-exchange Cross Sections and Modeling X-Ray Emissions for Ne8+ Colliding with H2 and He - P. F. Ma; H. Yin; B. Ren; T. Meng; J. Wang; Y. Wu; X. Tan; Y. Zhang; Y. Qi; K. Yao; J. Xiao; Y. Zou; et al. (The Astrophysical Journal)
Charge exchange is a predominant process in inelastic collisions in astronomical plasmas, influencing the charge state balance and leading to X-ray emissions when solar wind ions interact with neutral gas in astrophysical environments. Accurate analysis of these dynamic properties to diagnose the solar wind composition and velocities, as well as the spatial distribution of the heliospheric neutral gas, can be hindered by the limited availability of relevant electron capture studies in the corresponding energy range. The absolute total and $n$ -resolved state-selective cross sections of single electron capture have been measured in the collisional energy range from 2.8 to 40 keV u ^−1 , covering velocities corresponding to fast solar wind and coronal mass ejections. In comparison with existing atomic data, we observe good agreement with other results at overlapping energies. Based on the absolute $n$ -state electron capture cross sections, the absolute cross sections of photon emissions following charge exchange between Ne ^8+ and H _2 , as well as He gas, were determined for the potential applications in high-resolution X-ray spectra studies of solar wind charge exchange. This work serves as a benchmark for validating the theoretical calculations of charge exchange cross sections and astronomical plasma models, providing valuable insights into the investigation of soft X-ray emissions in solar wind plasma environments.